ESTRATÉGIAS APLICADAS NO ENSINO DA CONTABILIDADE: EVIDÊNCIAS DOS PLANOS DE ENSINO DE UMA UNIVERSIDADE PÚBLICA - Leandro Marques (Universidade Federal de Santa Catarina, 2019)
This study aimed to identify the teaching strategies that are applied most frequently in Accounting Graduation from a Public University from Santa Catarina, in the South Region of Brazil. We adopted the descriptive research as research methodology, with quantitative approach based on the documental analysis of courses’ lesson plans. We analyzed 614 lesson plans, referring to a period of sixteen semesters. The most frequently strategies were: exercises, lectures, dialoguing lectures, readings, seminars, discussion and debate and cases. We also verified that the most frequently didactic resources were data-show and blackboard. We find that lesson plans from basic courses showed several strategies when compared to other subjects. Finally, there was found differences in use of strategy according to the degree level of the professor teaching the course. Nevertheless, it is inferred that the teacher’s academic degree does not necessarily interfere in the adoption of varied teaching strategy, since teachers with doctorate ended up adopting a smaller repertoire of declared strategies.